2013
DOI: 10.1038/nature12687
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 3 coordinates commensal-bacteria-dependent intestinal homeostasis

Abstract: The development and severity of inflammatory bowel diseases (IBD) and other chronic inflammatory conditions can be influenced by host genetic and environmental factors, including signals derived from commensal bacteria1–6. However, the mechanisms that integrate these diverse cues remain undefined. Here we demonstrate that mice with an intestinal epithelial cell-specific deletion of the epigenome-modifying enzyme histone deacetylase 3 (HDAC3ΔIEC mice) exhibited extensive dysregulation of IEC-intrinsic gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
205
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(209 citation statements)
references
References 39 publications
4
205
0
Order By: Relevance
“…Commensal bacteriaderived signals also influence host epigenetic pathways, particularly through DNA and histone methylation [32][33][34][35][36] and histone acetylation and deacetylation [37][38][39][40][41] . The commensal microbiota produces multiple low-molecular-weight byproducts that modify the host cell epigenome and may alter the functional behavior of host cells.…”
Section: Special Issue (Mini Review) Gut Microbiota and Epigeneticsmentioning
confidence: 99%
“…Commensal bacteriaderived signals also influence host epigenetic pathways, particularly through DNA and histone methylation [32][33][34][35][36] and histone acetylation and deacetylation [37][38][39][40][41] . The commensal microbiota produces multiple low-molecular-weight byproducts that modify the host cell epigenome and may alter the functional behavior of host cells.…”
Section: Special Issue (Mini Review) Gut Microbiota and Epigeneticsmentioning
confidence: 99%
“…Antibiotic administration can impact transcript levels and histone modifications in IECs (Thaiss et al 2016); however, it's unclear if these changes are indirect effects caused by alterations to microbiota composition, direct effects of the antibiotic on host cells, or the effects of remaining antibiotic-resistant microbiota (Morgun et al 2015). Previous studies have shown that histone deacetylase 3 is required in IECs to maintain intestinal homeostasis in the presence of microbiota (Alenghat et al 2013) and that overall histone acetylation and methylation in the intestine is altered by microbiota colonization (Krautkramer et al 2016). However, the direct and specific effects of the microbiota on host CRRs and subsequent transcriptional responses in IECs remain unknown.…”
mentioning
confidence: 99%
“…Changes in DNA and histone modifications associated with epigenetic regulation have been detected in IBD patients (3,4,9,11,12), but direct links to the IBD intestinal pathology have not been established. However, recent work has shown that IEC-specific deletion of the histone deacetylase HDAC3 results in increased susceptibility to intestinal damage and inflammation, although specific molecular targets remain to be identified (13).…”
mentioning
confidence: 99%